2022
DOI: 10.1039/d1ta09013e
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Juncus derived carbon decorated with cobalt nanoparticles enables high-efficiency ammonia electrosynthesis by nitrite reduction

Abstract: Electrochemical nitrite (NO2–) reduction reaction (NO2RR) is not only a promising strategy to degrade harmful NO2– contaminant in the environment but an attractive alternative to the Haber-Bosch process for sustainable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…Our group experimentally demonstrated Co's high intrinsic activity and made significant progress by developing various Co catalysts such as Co-NCNT [408], Co-decorated pomelopeel-derived carbon [409], Co-decorated Juncus-derived carbon [410], Co-P alloy [413], Fe-doped Co3O4 nanoarray [411], and Co-containing spinels such as NiCo2O4 [414] and Co2AlO4 [415]. Wang's group also demonstrated that Co was active enough for NO3RR to produce NH3 (Fig.…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our group experimentally demonstrated Co's high intrinsic activity and made significant progress by developing various Co catalysts such as Co-NCNT [408], Co-decorated pomelopeel-derived carbon [409], Co-decorated Juncus-derived carbon [410], Co-P alloy [413], Fe-doped Co3O4 nanoarray [411], and Co-containing spinels such as NiCo2O4 [414] and Co2AlO4 [415]. Wang's group also demonstrated that Co was active enough for NO3RR to produce NH3 (Fig.…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionsmentioning
confidence: 97%
“…Similarly, uniformly and densely dispersed Co nanoparticles were successfully synthesized using the Juncus-derived carbon as support (Co@JDC; Fig. 21(c)) [410], and the hybrid catalyst performed well in NH3 synthesis performance (a yield of 2.8 ± 0.1 mol•h −1 •gCo −1 and an FE of 96.9% ± 2.1%) via NO2RR. We assembled a two-electrode electrolyzer using solar panels to collect solar energy to provide the voltage, with the graphite felt-supported Co@JDC as both the anode and cathode, and achieved up to 12 h of solar-driven NO2 − to NH3 conversion (Figs.…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionsmentioning
confidence: 97%
“…It also performs well in pre-treated wastewater for NH 3 generation from NO 3 − . This work provides us with an efficient catalytic material for NH 3 electrosynthesis from nitrate, and opens up a modern opportunity for the design and development of metal oxides with oxygen vacancies for the selective electroreduction of nitrogen oxides 47–49 and nitrites 2,4,50,51 into high-value NH 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The present work not only offers an earth-abundant catalyst material enabling high-efficiency NOto-NH 3 conversion under benign conditions, but would also open up a new avenue for the rational design and construction of Fe-based nanocatalysts toward NH 3 electrosynthesis applications via selective electroreduction of gaseous NO and nitrogen oxyanions present in aqueous environments. [70][71][72][73]…”
mentioning
confidence: 99%